Factors Associated with Psychosomatic Disorders Among Systemic Lupus Erythematosus (SLE) Patients During the Coronavirus Disease 2019 (COVID-19) Pandemic - Dina Elita; Alvina Widhani; Hamzah Shatri; Ikhwan Rinaldi; Rudy Hidayat; Teguh Harjono Karjadi; Rudi Putranto; Chyntia Olivia Maurine Jasirwan; Siti Setiati (Interna Publishing, 2024)
Background: The COVID-19 pandemic has affected physical and mental health. SLE patients are prone to psychosomatic disorders which can decrease their quality of life. This study aimed to determine the factors associated with psychosomatic disorders among SLE patients during the COVID-19 pandemic. Methods: This was a cross-sectional study of adult female SLE patients from the outpatient clinic of Cipto Mangunkusumo Hospital, Jakarta. Data regarding psychosomatic disorders were collected using SCL-90 questionnaires, and data on demographic factors, perception of COVID-19 conditions, perception of stress, psychosocial stressors, disease activity (MEX-SLEDAI), and treatment were also collected. Bivariate analysis for categorical data was conducted using the Chi-square test. Variables with a p-value <0.25 were further analyzed with logistic regression, and p-values <0.05 were considered significant. Meanwhile, data per domain were analyzed using the Mann-Whitney test with p-values < 0.05 being considered significant. Results: There were 200 female SLE patients recruited. More than half of the subjects (54%) experienced psychosomatic disorders. From multivariate analysis, high educational levels, moderate and high psychosocial stressors, and very severe disease activity levels were found to be significantly associated with the occurrence of psychosomatic disorders in SLE patients during the COVID-19 pandemic. Conclusion: Education level, psychosocial stressors, and disease activity level were found to be significantly associated with the occurrence of psychosomatic disorders in SLE patients during the COVID-19 pandemic.